ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¨ØªÙ‚Ù†ÙŠØ© Ø«Ù„Ø§Ø« Ø®Ø·ÙˆØ§Øª Ù„Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø³ØªØ§Ù† Ø§Ù„ØÙƒÙ…Ø© Ø¯ÙˆÙ…ÙÙŠ Ø§ØºÙˆÙ†Ø¬ ÙƒÙ…Ø¨Ø§Ù†Ø¬ Ø¨Ø§Ù‡Ùˆ Ù„Ø§Ù…ÙˆÙ†Ø¬Ø§Ù† - Khoirotun Ni'mah; Ida Latifatul Umroh; Miftahul Jannah (Al-Fakkaar, 2023)
Speaking skills are basic skills in linguistics because one of the functions of language learning is to be able to communicate properly and correctly. In Arabic there are four language skills, namely listening, speaking, writing and reading. Of the four skills, which researchers focus on in this study is speaking skills. This research is motivated by the difficulty of students in conveying an utterance that will be presented and the lack of ability to speak in Arabic. Therefore, the researcher provides the application of three step iterview technique to improve speaking skills in Arabic. The type of this research is quantitative research, while the research design used is pre-experimental in the form of one group pretest-posttest design. The data collection uses three techniques, namely observation, interviews and tests. While the data analysis used descriptive data analysis techniques and inferential data analysis. With the application of three step interview technique, it is expected to be able to improve students' speaking skills in Arabic.